A feasibility and pilot trial of computerised cognitive behaviour therapy for depression in adolescents: lessons learned from planning and conducting a randomised controlled trial. Issue 3 (12th September 2016) - Tindall, Lucy; Varley, Danielle; Wright, Barry
Abstract : Purpose: The purpose of this paper is to focus upon the challenges faced by a research team when conducting a computerised cognitive behaviour therapy (CCBT) trial for adolescents with low mood/depression and how solutions were sought to eliminate these difficulties in future child and adolescent mental health clinical research. Design/methodology/approach: The authors have presented a number of problems faced by the research team when conducting a randomised controlled trial (RCT) concerning adolescents with low mood/depression. Findings: From examining the problems faced by the research team, the authors have provided key pieces of advice for prospective adolescent mental health RCTs. This advice includes developing clear project plans, setting strategies to encourage and maintain study information in the community and support recruitment, and keeping your organisation appraised of study needs and network and involve governance departments, IT and finance departments in these discussions early. Originality/value: RCTs, particularly those focusing on child and adolescent mental health, can face a number of difficulties throughout its stages of completion (from protocol development to follow-up analysis). Studies involving the use of technologies add a layer of complexity to this. This review will be of value to researchers aiming to run a high-quality RCT concerning child and adolescent mental health.